2015
DOI: 10.35196/rfm.2015.1.17
|View full text |Cite
|
Sign up to set email alerts
|

CARACTERIZACIÓN MORFOLÓGICA Y FENOLÓGICA DE ESPECIES SILVESTRES DE FRIJOL (Phaseolus)

Abstract: Con el objetivo de generar información útil para el incremento y conservación de accesiones de frijol silvestre, se realizó la caracterización morfológica y fenológica de 12 especies silvestres de Phaseolus. Las especies de procedencia tropical y subtropical se sembraron en invernadero y las oriundas de sitios templados en campo bajo estructura de malla sombra. En la caracterización se utilizaron los descriptores varietales de frijol común (Phaseolus vulgaris L.) del Servicio Nacional de Inspección y C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…This result is in accordance with a previous study by Sinkovic et al [ 15 ], who indicated that most of the accessions from South Eastern Europe had 2–3 seeds per pod. In addition, the average number of seeds per pod in a wild population of runner bean was 4.2 [ 40 ]. Therefore, the lines evaluated in this study exhibited intermediate values of seeds per pod, which may be due to various factors such as high air temperatures, self-incompatibility and the lack of pollinators, since it has been reported that the number of seeds per pod can increase up to 15% with the presence of pollinators [ 4 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in accordance with a previous study by Sinkovic et al [ 15 ], who indicated that most of the accessions from South Eastern Europe had 2–3 seeds per pod. In addition, the average number of seeds per pod in a wild population of runner bean was 4.2 [ 40 ]. Therefore, the lines evaluated in this study exhibited intermediate values of seeds per pod, which may be due to various factors such as high air temperatures, self-incompatibility and the lack of pollinators, since it has been reported that the number of seeds per pod can increase up to 15% with the presence of pollinators [ 4 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The morphological and physiological changes that a plant experiences during its biological cycle define the stages of development [ 40 ]. The analysis of the phenological development for the Chilean lines of runner bean evaluated in this study is shown in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…El Perú es un país con una gran diversidad de frijol común, que es cultivado principalmente en las regiones costeras y andinas (MIDAGRI, 2024). Sin embargo, pese a su importancia ecológica y económica, es preciso generar mayor información sobre su valor agronómico y alimentario (Mex-Álvarez et al, 2021), considerando que los rasgos morfológicos desempeñan un papel importante en la clasificación e identificación de especies, razas y variedades vegetales (Meza et al, 2015), porque permite cuantificar y estructurar la variabilidad genética existente, en función de su origen, hábito de crecimiento, floración, rendimiento y respuesta a plagas y enfermedades (Chiorato et al, 2006).…”
Section: Introductionunclassified
“…El conocimiento detallado de las relaciones filogenéticas de Phaseolus es esencial en el entendimiento del origen y diversificación genética (Smýkal et al, 2015), así como para su conservación, aprovechamiento y su mejoramiento genético (López Soto et al, 2005;Meza-Vázquez et al, 2015). Este trabajo se llevó a cabo para analizar las relaciones filogenéticas de especies de Phaseolus de México con base en marcadores moleculares de ADN cloroplástico.…”
Section: Introductionunclassified